The Moon Hoax? Conspiracy Theories on Trial - Eversberg, Thomas; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book is about the American moon-landings - and about the doubts expressed ever since concerning the reality of these landings. Were the moon landings really just a huge and cleverly executed hoax? Eversberg explains the best-known claims and conspiracy theories and analyses the evidence with the help of detailed full-colour images, as well as numerous film documents that can be accessed directly from the book. He addresses both the persistent older claims and more recently devised doubts. The book will inform and entertain a wide range of readers interested in space exploration and tells a gripping story covering physics, politics and history.
Foreword -- Prologue - The Conspiracy of the Faked Moon Landings -- Russians, Rockets and Election Campaigns -- Proof I The Dilemma -- Stars are Missing in the Sky -- But Look! The Flag Flutters! -- A Lamp - Oblique Shadows -- Manipulation of the Pictures -- Is Everything in Slow Motion? -- Telescopes Can See Everything -- Warning! Hazardous Radiation! -- Too Hot, Too Cold -- The Lander's Exhaust Plume and its Crater -- Anything Else? -- Proof II - Rocks, Photos, and Stars -- What Can We Learn? -- Technology, Money, and the Return to the Moon -- Appendix A - Apollo Drawings -- Appendix B - The Astronauts of the Moon Landing Missions.
Keywords: Engineering; Solar system; Aerospace engineering; Astronautics; Technology and Engineering; Space Physics; Aerospace Technology and Astronautics